Multi-fractal analysis of the earth’s electromagnetic field time variations caused by the powerful geospace storm occurred on September 7-8, 2017 - Chernogor, L.F.; Garmash, K.P.; Lazorenko, O.V.; Onishchenko, A.A. (Вопросы атомной науки и техники, 2018)
The results of multi-fractal analysis of time variations of the Earth’s electromagnetic field caused by the powerful geospace storm occurred on September 7-8, 2017 were considered. To obtain the most detailed results, the multifractal detrended fluctuation analysis, the Hurst exponent in sliding time domain window and the continuous wavelet transform were simultaneously applied. The set of numerical characteristics, which describe the peculiarities of the Earth’s electromagnetic field time variations, was estimated.